2012
DOI: 10.1016/s2255-4971(15)30088-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Patellar Height Measurement Methods From Digital Radiography

Abstract: Objective: To analyze the most common methods for measuring patellar height and the impact of observer experience in correlations with the other observers using digital radiography. Methods: Sixty digital radiographs of the knee in lateral view were analyzed by four observers: a physician in the second year of medical residence in orthopedics (R2); a physician in the third year of medical residence in orthopedics (R3); an orthopedic surgeon who was a specialist in knee surgery (SK); and a radiologist who was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
1
16
0
2
Order By: Relevance
“…The reason why the authors chose the C-D as the benchmark over the IS method are the following: C-D is a simple, reproducible method validated in asymptomatic patients and reported sensitivity and specificity are similar to other CRRs. 9 Experience is proven to increase reliability of patellar height measurements, 13 and C-D is the mskR's preferred method to determine patellar height. In this study, C-D was measured by the same trained mskR and proved to have excellent intrarater reliability.…”
Section: Discussionmentioning
confidence: 99%
“…The reason why the authors chose the C-D as the benchmark over the IS method are the following: C-D is a simple, reproducible method validated in asymptomatic patients and reported sensitivity and specificity are similar to other CRRs. 9 Experience is proven to increase reliability of patellar height measurements, 13 and C-D is the mskR's preferred method to determine patellar height. In this study, C-D was measured by the same trained mskR and proved to have excellent intrarater reliability.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, both Nizić et al (ICC ¼ 0.93-0.95) and Gracitelli et al (ICC ¼ 0.603-0.809) found IS to have the best interobserver reliability among the four measurement tools on XR. 28,29 However, there is a mixture of reported data on the patellar height ratio with the next best ICC on XR. 19,[29][30][31][32] BP on MRI had the worst interobserver reliability in our study.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 However, there is a mixture of reported data on the patellar height ratio with the next best ICC on XR. 19,[29][30][31][32] BP on MRI had the worst interobserver reliability in our study. Lee et al found similar results with BP on CT and MRI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations